Higher rating of perceived exertion and lower perceived recovery following a graded exercise test during menses compared to non-bleeding days in untrained females - Delp, Morgan; Chesbro, Grant A.; Pribble, Brian A.; Miller, Ryan M.; Pereira, Hugo M.; Black, Christopher D.; Larson, Rebecca D. (Frontiers in Physiology, 2024)
Previous studies examining the effects of the MC on aerobic performance and subjective measures of aerobic performance show conflicting results. Purpose: The study examined how the MC affects measures of aerobic performance within female participants and compared to male participants assessed at similar time intervals. Methods: Twenty-one participants (12F, 9M), completed a graded-exercise-test (GXT). The female participants were tested during the early follicular (EF), ovulatory (O), and mid-luteal (ML) phases of the MC. Male participants were included as the control group and were randomly assigned to a menstrual cycle phase for each visit. During the GXT, oxygen consumption (VO2max), respiratory exchange ratio (RER), max heart rate (HRmax), lactate, and rating of perceived exertion (RPE) were determined. Twenty-four hours post-exercise, perceived recovery (PRS) was assessed. MC phase was estimated using basal body temperature (BBT) in females. Results: The male participants obtained a higher peak power and VO2max compared to the female participants (p<0.05). All objective measures of aerobic performance did not significantly differ across the MC phases or time points that were tested. In the untrained female participants, an effect of MC phase on RPE was found, with RPE being higher at EF (8.92 ± 0.79) compared to O (7.67 ± 1.23; p<0.05) and ML (7.75 ± 1.06; p<0.05). In addition, an effect of MC phase on PRS was found, with perceived recovery being lower at EF (6.83 ± 0.94) compared to O (8.83 ± 1.12) and ML (8.67 ± 0.65) (all p<0.005) for the untrained female participants. No significant differences in RPE and PRs between tests were found in the male participants. The female participants had lower perceived recovery following EF (6.83 ± 0.94) compared with the male participants (9.00 ± 1.00; p < 0.001). Conclusion: The female participants perceived greater exertion during a GXT and impaired recovery following a GXT in EF compared to O and ML. These results may be attributed to either a drop in female sex hormone concentrations or discomfort associated with menses. TFuture studies using subjective parameters such as perceived exertion to track the internal load of training in naturally menstruating females should consider menses.